Mechanical property and analysis of asphalt components based on molecular dynamics simulation - Li, Rui (2018)
The asphalt-aggregate interface interaction plays a significant role in the overall performances of asphalt mixture. In order to analyze the chemical constitution of asphalt effects on the asphalt-aggregate interaction, the average structure C64H52S2 is selected to represent the asphalt, and the colloid, saturated phenol, and asphaltene are selected to represent the major constitutions in asphalt. The molecular models are established for the three compositions, respectively, and the Molecular Dynamics (MD) simulation was conducted for the three kinds of asphaltene-aggregate system at different presses. Comparing the value of Young modulus of these three polymers, the maximum modulus value of asphaltene was 2.80 GPa, the modulus value of colloid was secondary, and the minimum modulus of saturated phenol was 0.52 GPa. This result corresponds to conventional understanding.